Should there be future people? A fundamental question for climate change and intergenerational justice. (17th February 2017) - Sanklecha, Pranay
Abstract : The effects of climate change will be felt far into the future, long after currently living people have stopped existing. A popular way of understanding what this means ethically is to conceptualize the issue in terms of intergenerational justice: currently living people have duties of justice toward future generations to not wrongfully harm them, or duties to reduce the risk of violating the rights future people will have when they exist. In this article I show that this depends on assumptions about the existence, identity, and number of future people. I argue for the relevance and importance of ethically investigating these assumptions; in particular of asking: should humanity continue to exist? I argue that this ethical investigation is necessary to properly and fully understand the ethical challenges that climate change creates. WIREs Clim Change 2017, 8:e453. doi: 10.1002/wcc.453 This article is categorized under: Climate, Nature, and Ethics > Climate Change and Human Rights